Magnetic MIL-101-SO3H: a highly efficient bifunctional nanocatalyst for the synthesis of 1, 3, 5-triarylbenzenes and 2, 4, 6-triaryl pyridines. Issue 102 (21st October 2016) - Boroujeni, Mahmoud Borjian; Hashemzadeh, Alireza; Faroughi, Mohammad-Tayeb; Shaabani, Ahmad; Amini, Mostafa Mohammadpour
Abstract : A magnetic MIL-101-SO3 H was synthesized and successfully used as a highly active nanocatalyst for the synthesis of 1, 3, 5-triarylbenzenes and 2, 4, 6-triaryl pyridines. Abstract : A magnetic MIL-101-SO3 H was synthesized and successfully used as a highly active nanocatalyst for the synthesis of 1, 3, 5-triarylbenzenes and 2, 4, 6-triaryl pyridines. The prepared nanocatalyst was characterized by Fourier transform infrared spectroscopy, scanning electron microscopy, energy-dispersive X-ray and X-ray powder diffraction. It is found that the catalyst can be easily separated from the reaction mixture by an external magnetic field and recycled several times without a significant loss of activity.